Performance Reporting Choices after the Adoption of IAS 1 Revised: Comparative Evidence from Europe and the USA - Doni, Federica; Rossetti, Silvia; Verona, Roberto (International Journal of Economics and Financial Issues, 2017)
Motivated by the issuance of International Accounting Standard 1 revised, this paper investigates reporting choices on the Comprehensive Income of listed companies from Europe and the USA. This research aims at verifying the effects of the requirements issued by the International Accounting Standard 1 revised in improving performance evaluation towards the convergence between European and American accounting standards, Our research tests the correlation between the choice of Income Statement format and different variables, such as the size of companies, sign of Other Comprehensive Income, leverage and status of a US listing. This paper also evaluates the effect of Comprehensive Income on financial performance by calculating the Return On Equity. The main findings underline that the format of Income Statement and the “location” of the Comprehensive Income can be interpreted both as factors that can influence the choices of investors and as a tool available to managers to alter the communication of the firm's performance choices. Keywords: Comprehensive Income; convergence; performance JEL Classifications: M10, M16, M40, M41